2017 IEEE Globecom Workshops (GC Wkshps) 2017
DOI: 10.1109/glocomw.2017.8269114
|View full text |Cite
|
Sign up to set email alerts
|

Throughput Maximization Scheduling Algorithm in TSCH Networks with Deadline Constraints

Abstract: Time Slotted Channel Hopping (TSCH), defined among the operating modes in IEEE 802.15.4-2015 standard, was established to offer a guaranteed quality of service for deterministic industrial type applications. However, the standard only provides a framework but it does not mandate a specific scheduling mechanism. In this paper, we formulate the NP-hard scheduling problem in terms of maximizing the throughput with deadline constraints and at the same time satisfying interference constraints in TSCH Networks. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In almost all previous TSCH scheduling, authors either assume that the impact of link qualities or channel variations on performance are negligible (such as [7][8][9][10][11][12][13][14]), or that the instantaneous and complete channel information is available (such as [15][16][17]), or else the channel is modeled quasi-static (such as [18][19][20]). For example, in [15 and 16], it is assumed that the instantaneous CSI is fully measurable and available, therefore one can use an offline method and calculate the optimal scheduling for a TSCH network by the exact rate of packets to be sent over each link.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In almost all previous TSCH scheduling, authors either assume that the impact of link qualities or channel variations on performance are negligible (such as [7][8][9][10][11][12][13][14]), or that the instantaneous and complete channel information is available (such as [15][16][17]), or else the channel is modeled quasi-static (such as [18][19][20]). For example, in [15 and 16], it is assumed that the instantaneous CSI is fully measurable and available, therefore one can use an offline method and calculate the optimal scheduling for a TSCH network by the exact rate of packets to be sent over each link.…”
Section: B Related Workmentioning
confidence: 99%
“…To the best of our knowledge, there are many studies which present new scheduling methods for TSCH networks without considering the impact of CSI (such as [7][8][9][10][11][12][13][14]). We have seen that in some schemes authors assume that perfect non-causal knowledge of CSI is available for the scheduling process (such as [15][16][17]) and in others prior statistical knowledge of link qualities is utilized in order to improve performance (Such as [18][19][20]). Although such assumptions in earlier scheduling algorithms, where channel status is available or constant, enable mathematical tractability of the scheduling problem, they are not realizable in real-world systems due to the difficulty in predicting random and timevarying wireless channel conditions.…”
Section: Motivationmentioning
confidence: 99%
“…It ensures high reliability and efficiency while delivering the data packets. |In [21], an efficient scheduling technique is adopted in TSCH networks to provide high throughput and minimum delay considering the deadline constraints. A scheduler based on genetic algorithm is proposed to provide optimal throughput and minimum complexity.…”
Section: Related Workmentioning
confidence: 99%
“…The scheduling algorithms depend upon noncausal information about instantaneous channel qualities, such as the signal-to-noise ratio (SNR) [12]. Furthermore, the TSCH-based scheduling is performed based on the maximization of the network's throughput [13,14]. In addition, some other scheduling algorithms utilize previous statistical information on link qualities, such as the expected number of transmissions (ETX) or the packet error rate (PER), to improve the average packet delivery ratio (PDR) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, in real applications of wireless networks, the channels exhibit random behaviours with time-varying conditions. In some papers, we have found that the authors considered the variation of channel status, which means that the CSI was considered for performing the scheduling tasks [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%